A spatial analysis of the drug phenomenon in Asia (2021) (Texas Journal of Multidisciplinary Studies, 2022)
The aim of the research is to study the phenomenon of drugs in some of the countries of the Asian continent, the most prevalent drugs, according to the data of the International Drug and Crime Report for the year (2021), by knowing the most prevalent Asian countries for drugs, as well as knowing the most prevalent types of drugs on the continent, and the age groups most vulnerable to drug abuse, In addition to knowing the effects arranged on drug users on the continent, and put forward many proposals that may contribute to reducing the rise of the drug phenomenon on the continent, and with regard to the research methodology, it has been relied on the descriptive analytical method in studying many of the developments and variables that accompanied the geographical analysis of the drug phenomenon. In some countries of the continent, the data of the Drug Report (2021) was relied upon in order to give an accurate and clear picture of the spread of the drug phenomenon on the continent. The research revealed that the most drug-producing and consuming countries are Afghanistan, Pakistan, Laos, and Myanmar and that the continent of Asia is rife with opium and cannabis-type drugs. Amphetamine-type stimulants in Asia, and the research also showed that the most prevalent types of drugs in some countries of the Asian continent are opium and cannabis, especially during the period of the Covid-19 pandemic, and cocaine declined in varying proportions. This could be partly due to a shift in demand towards synthetic drugs in their places of existence, or it could be due to the increased effectiveness of global measures to address the drug phenomenon and its role in its decline.